HEALTH AND EDUCATION OF A PHYSICIAN: TWO PARTS OF THE SUCCESS - S. Yu. Martsevich; L. Yu. Drozdova; V. P. Voronina (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate a prevalence of cardiovascular risk factors among physicians, awareness about their own cardiovascular risk factors as well as their knowledge about actual clinical guidelines.Material and methods. 71 physicians (age 44,7±9,7 y.o.) practicing in city of Nizhni Novgorod were included into the study. They were examined to reveal cardiovascular risk factors and interviewed about main methods of cardiovascular diseases treatment and prevention.Results. Arterial hypertension (HT) prevalence among physicians was 38%, awareness about HT occurrence - 28%, own blood pressure control - 11% of physicians. The prevalence of hypercholesterinemia was 44%, 65% of physicians did not know their own plasma cholesterol level. Physicians had obesity or overweight in 21% and 42% respectively. 91% of physicians demonstrated knowledge about cardiovascular risk factors, 90% and 79% of them were sure regarding possibility to achieve target blood pressure and lipid levels, respectively.Conclusion. High prevalence of HT, hypercholesterinemia, and overweight were found out among physicians despite of their knowledge of actual clinical guidelines on cardiovascular diseases therapy and prevention.